Generation and Experimental Stress Analysis of Elliptical Gears with Combined Teeth (Journal of Engineering, 2019)
In this study, generation of elliptical gears with different teeth profiles of crowned involute, double circular arc (DCA), and combined (crowned involute with DCA) has been developed. The resulting mathematical equations have been computerized and feed to CNC end mill machine to manufacture elliptical gear models with different profiles. These models are investigated in plane polariscope to show the resulting stresses under certain load. Comparison of photo-elastic stress results shows that combined elliptical gears with DCA side as a loaded side have a minimum resulting contact stress with a reduction percentage of 40% compare with contact stresses in counterpart elliptical gear of involute profile (which is commonly used in several applications). In this case, bending tooth stress reduction is 47.05% compare with involute elliptical gear. While the reduction in bending stresses of combined elliptical gear becomes higher (52.94% lower than involute gear) when crowned involute side is the loaded side, but the contact stress reduction in this case becomes lower (20% relative to involute gear). Maximum reduction in bending stress can be obtained when single profile of DCA type is used with a reduction of 64.7% relative to involute gear. Therefore; when the application requires a high contact stress resistance, combined profile can be used with DCA side as a loaded side. While in the applications that require high bending stress resistance, DCA profile can be used.